Scout Participation in Public Health Activities in the Jabodetabek Region in 2020 - P. A. Kodrat Pramudho; Armalia Reny (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Health problems cannot be solved by health officials alone. The scout movement with millions of members throughout Indonesia clearly has a very important role in this. Scout members as millennial youth can be important agents of change, both for fellow youths, for parents and their families as well as for society as a whole. The members of the Ventura Scouts (16-20 years) andRover Scouts (20-25 years) in Indonesia number around 3.6 million (16% of 23 million). The study aims to observe the participation of the Ventura Scout and Rover Scouts who carry out various activities in the public health in the Jabodetabek area and which media cover/report on these Scouting activities. The research is qualitative in nature by observing news of Scout involvement in the public health activities in electronic mass media, print media and online media from January to June 2020. To complete the information, the researchers conducted in-depth interviews with several connected coaches and scouts. The analysis is carried out simply by comparing which media do the most news coverage/broadcasting about scout activities in the publicc health activities, and what motivations make scouts involved in public health activities. The research results showed that the of Ventura Scoutand Pandega Scouts were heavily involved in the public health activities, especially during the Covid19 pandemic, among others, distributing masks, becoming counselors, becoming role models. It turned out that online media was mostly followed by print and electronic media which covered and reported on the Ventura Scout and Rover Scout activities. This is also because the Ventura Scoutand Pandega Scouts are contributors to online media news, moreover Scouts have the tagline